KAJIAN PENURUNAN TITIK LELEH LILIN LEBAH (Apis cerana) DALAM PEMBUATAN MARGARIN OLES RENDAH KALORI 1) [Study on Decreasing the Melting Point of Beeswax (Apis cerana) in the Production of Low -Calorie Margarine] - Zita L. Sarungallo; Soewarno T. Soekarto; Slamet Budijanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2002)
Beeswax has been used to replace fat in order to produce low calorie margarine; however, the quality of the product was still low. To produce a good quality of beeswax-containing margarine, the melting point of beeswax must be lowered close to human body temperature. The o objectives of the research were : (1) to study the effect of addition of palm olein oil, fat solvent, emulsifier and stabilizer on the decrease of the melting point of beeswax, (2) to study the effect of enzymatic transesterification process, and (3) to produce margarine with low melting point and organoleptically acceptable. The results of the study revealed that addition of margarine ingredient lowered the melting point and solid fat content of the mixture, eventhough the melting point only reduced by 10°C, i.e. 64°C to 54°C. The process of transesterification was carried out on beeswax and palm olein with ratio of 50:50 and 40:60 using lipozyme IM 20 transesterification from Mucor miehei as a catalyst at 78,5°C for 24 hours with agitation at 200 rpm. Using this transesterification condition, the ratio of beeswax and palm oil of 50,50 produced fat with iodine value of 36,3 acid value of 18,5, free fatty acid of 8.45%, and melting point of 53°C, while ratio of 40: 60 produced fat with iodine value of 42,5, acid value of 15.44, free fatty acid of 7.24% and the melting point of 52°C produce fat with iodine value of 36,31 and 42,51, acid value of 18,5 and 15,44, free fatty acid of 8,45% and 7,24% at the melting point of 53°C and 52°C. It also produced solid fat content (40oC) of 26,06% and 18,13%, with the consistency of 9,75 mm sec/gr and 13,96 mm sec/gr, respectively. The transesterification and non-transesterification beeswax with palm olein oil also can produce a low calorie margarine with the value of 12,3% - 50,5% lower than the comercial margarine, with the same physical and sensory characteristics.